Comprehending of florfenicol (form A) dissolution behavior in aqueous low alcohol blends: Solubility, solvation thermodynamics as well as inter-molecular interactions. (January 2023) - Liu, Ying; Zhao, Hongkun; Zhu, Peizhi; Farajtabar, Ali; Jouyban, Abolghasem; Acree Jr, William E.
Graphic abstract: Highlights: Weak interactions between florfenicol and solvent were studied by using IGMH. Florfenicol solubility in three aqueous alcohol solutions was determined and correlated. Solvation behavior of florfenicol in solutions was studied via IKBI and EHSA technique. Solvent effect was studied through KAT-LSER model. Abstract: The quantitative studies of the molecular surface and independent gradient model that was on the basis of the Hirshfeld partition (IGMH) were adopted herein to qualitatively elucidate the electrostatic characteristics of the basicity as well as acidity of florfenicol, together with the inter-molecular interactions in isopropanol/methanol/ethanol + water systems. The results of this study indicated that the >NH, O, and –OH groups in the florfenicol molecule had priority over forming hydrogen bonds with the alcohol solvents compared with the other function groups in the molecule. The shake-flask method was utilized to examine florfenicol solubility under pressures of 101.2 kPa and raised temperatures (278.15–318.15 K). In the fluctuation of solubility magnitudes, the polarizability-dipolarity, solubility parameter, and hydrogen basicity/acidity of solutions all played important roles. With a relative mean deviance of ⩽ 8.41 %, the modified Wilson, the van't Hoff Jouyban–Acree, the Jouyban–Acree, and the Apelblat models all demonstrated good correlation values for the solubility. The approach of extended Hildebrand solubility was used to examine the solvation behavior at 298.15 K. This resulted in a RAD that was no more than 1.26 percent. The method of Kirkwood-Buff integral was used here to inspect the preferred solvation of florfenicol. In both the rich and the intermediate compositions of methanol/isopropanol/ethanol, the florfenicol is solvated preferentially by the alcohols with positive solvation parameters.